Breaking down insect stoichiometry into chitin-based and internal elemental traits: Patterns and correlates of continent-wide intraspecific variation in the largest European saproxylic beetle. (July 2020) - Orłowski, Grzegorz; Mróz, Lucyna; Kadej, Marcin; Smolis, Adrian; Tarnawski, Dariusz; Karg, Jerzy; Campanaro, Alessandro; Bardiani, Marco; Harvey, Deborah J.; Méndez, Marcos; Thomaes, Arno; Vrezec, Al; et al.
Abstract: Stoichiometric, trophic and ecotoxicological data have traditionally been acquired from patterns of variation in elemental traits of whole invertebrate bodies, whereas the critical issue of the extracellular origin of some portion of elements, such as those present in ingested food and internal organs, has been ignored. Here we investigated an unexplored, yet crucial, question relating to whether, and to what degree, metals from two major body fractions: exoskeleton (elytra) and internal (body organs with gut material present in abdomens), are correlated with each other in wild populations of the largest European saproxylic insect, the Stag Beetle Lucanus cervus, and how metals from these two fractions vary with insect size and local habitat conditions. We examined the continent-wide variation in the concentrations of 12 chemical elements (Ca, Mg, K, Na, Mn, Fe, Zn, Cu, As, Cd, Pb and Ni) measured in the elytra and abdomen of specimens from 28 populations inhabiting an urban-woodland habitat gradient across the species' entire distributional range from Spain to Russia. Across populations, elemental concentrations (except Ni and Pb) were 2–13 times higher in abdominal samples than in elytra, and the magnitude of these differences was related to both insect size and local habitat conditions. Smaller individuals from both woodland and urban habitat tended to have higher concentrations of trace elements (Zn, As, Cd, Pb and Ni). The concentration of only six elements (Mg, K, Na, Mn, Cd and Ni) was correlated in the elytra and abdomen at the individual and population levels, implying a limitation to the broader applicability of elytra as a surrogate for internal elemental pools. We highlight that in non-feeding adult saproxylic beetles, minerals, acquired during the larval stage, may be concentrated in the large quantities of residual body fat. Graphical abstract: Image 1 Highlights: Smaller beetles have higher concentrations of Zn, As, Cd, Pb and Ni. Mg, K, Na, Mn, Cd and Ni in the elytra and abdomens were correlated. Ca, Mg, K, Na, Mn, Fe, Zn, Cu, As and Cd were 2–13 times higher in abdomens. Minerals/trace metals may be concentrated in the large quantities of residual body fat. Abstract : Our study emphasizes that in non-feeding adult saproxylic beetles, minerals/trace metals, acquired during the larval stage, may be concentrated in the large quantities of residual body fat.